Analysis of Fish Catch Diversity Index on Purse Seine Vessels in Indonesia Fisheries Management Area 718 (IFMA-718) - Fadli Alfarisi R; Perangin-angin, Robet; Sari, Ratih Purnama; Sugiono; Nurlaela, Eli (Coastal and Marine Journal, 2024)
Indonesia Fisheries Management Area 718 (IFMA-718), located in the Arafura Sea, is known for its high marine biodiversity and serves as a strategic fishing ground. However, the lack of fishing gear selectivity in this area poses a significant threat to the sustainability of marine resources. This study aims to evaluate the selectivity of purse seine fishing gear through biodiversity analysis using the Shannon-Wiener diversity index (H’), evenness index (E), and dominance index (C). Data collection was conducted from September 2023 to March 2024 in the Arafura Sea using a 149 GT purse seiner. Catch data were categorized into target species, bycatch, and discards. The results showed that the values of H’ ranged from 0.77 to 1.40, E values were mostly greater than 1, and C values were below 0.5. These findings indicate a high species diversity and evenness, alongside low dominance, suggesting a relatively balanced community structure. However, such diversity also reflects the low selectivity of the fishing gear, which captures both target and non-target species, including demersal and benthic organisms. In conclusion, the purse seine gear used in IFMA-718 is considered to have low selectivity and is potentially harmful to non-target marine ecosystems. This study provides essential insights for improving selective fishing practices and implementing sustainable fisheries management in the region.